Cystic Fibrosis Pigs Develop Lung Disease and Exhibit Defective Bacterial Eradication at Birth - Stoltz, David A (2010)
Lung disease causes most of the morbidity and mortality in cystic fibrosis (CF). However, understanding its pathogenesis has been hindered by lack of an animal model with characteristic features of CF. To overcome this problem, we recently generated pigs with targeted CFTR genes. We now report that, within months of birth, CF pigs spontaneously develop hallmark features of CF lung disease including airway inflammation, remodeling, mucus accumulation, and infection. Their lungs contained multiple bacterial species, suggesting an equal opportunity host defense defect. In humans, the temporal and causal relationships between inflammation and infection have remained uncertain. To investigate these processes, we studied newborn pigs. Their lungs showed no inflammation, but were less often sterile than controls. Moreover, after intrapulmonary bacterial challenge, CF pigs failed to eradicate bacteria as effectively as wild-type pigs. These results suggest that impaired bacterial elimination is the pathogenic event that initiates a cascade of inflammation and pathology in CF lungs. Finding that CF pigs have a bacterial host defense defect within hours of birth provides an opportunity to further investigate pathogenesis and to test therapeutic and preventive strategies before secondary consequences develop.